Aggregation with a double non-convex labor supply decision: indivisible private- and public-sector hours - Aleksandar Vasilev (Ekonomia, 2016)
This paper explores the problem of non-convex labor supply decisions in an economy with both private and public sector jobs. To this end, Hansen (1985) and Rogerson's (1988) indivisible-hours framework is extended to an environment featuring a double discrete labor choice. The novelty of the study is that the micro-founded representation obtained from explicit aggregation over homogeneous individuals features different disutility of labor across the two sectors, which is in line with the observed difference in average wage rates (OECD 2011). This theory-based utility function could be then utilized to study labor supply responses over the business cycle.
Additional information: Accepted for publication, forthcoming.
Keywords: J22; J30; J45; 330; indivisible labor; public employment; aggregation; elasticity of labor supply